Essentials of school education in the United Arab Emirates (The Emirates Center for Strategic Studies and Research, 2012)
Essentials of School Education in the United Arab Emirates examines various vital issues at play in the educational sector, including the role of national policies and legislation in developing the education system and the relationship between Emirati society and the education process.